Increase in the dislocation density and yield stress of the Ti50Ni50 alloy caused by thermal cycling. (2017) - Churakova, Anna; Gunderov, Dmitry
Abstract: Using the methods of transmission electron microscopy (TEM), X-Ray diffraction (XRD) and tensile mechanical testing, comparative studies of the effect of thermal cycling on the structure and properties of the coarse-grained (CG) and ultrafine-grained (UFG) alloy Ti50 Ni50 are performed. It is found that under the action of repeated thermal cycling, a greater reduction in the width of martensite plates occurs in the UFG alloy structure than in the CG alloy structure. It is shown that under thermal cycling, in martensite plates there form composite (001)B19' nanotwins with a size of several nanometers. Analysis of the mechanical testing results demonstrates that under thermal cycling in the UFG state there occurs a more noticeable increase in yield stress than that in the CG state, which is accounted for by a more intensive dislocation generation in the UFG material.